2011
DOI: 10.1089/scd.2010.0041
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein Ibα Receptor Instability Is Associated with Loss of Quality in Platelets Produced in Culture

Abstract: The development of culture processes for hematopoietic progenitors could lead to the development of a complementary source of platelets for therapeutic purposes. However, functional characterization of culture-derived platelets remains limited, which raises some uncertainties about the quality of platelets produced in vitro. The aim of this study was to define the proportion of functional platelets produced in cord blood CD34+ cell cultures. Toward this, the morphological and functional properties of culture-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 32 publications
7
27
3
Order By: Relevance
“…Platelets were defined by flow cytometry as events that had similar size (forward scatter) and surface (CD41 and CD42b) marker expression as blood platelets (Figure 3B, Supplementary Figure 2). While all CD42b + CDPs expressed CD41, only a fraction of CD41 + CDPs expressed CD42b as shown previously (Supplementary Figure 3) 12 . Using this protocol, we generated approximately 60 CD41 + CD42b + platelets and 30 CD41 + CD42b + megakaryocytes on Day 14 for every CD34 + cells seeded on Day 0 (Figure 3C).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Platelets were defined by flow cytometry as events that had similar size (forward scatter) and surface (CD41 and CD42b) marker expression as blood platelets (Figure 3B, Supplementary Figure 2). While all CD42b + CDPs expressed CD41, only a fraction of CD41 + CDPs expressed CD42b as shown previously (Supplementary Figure 3) 12 . Using this protocol, we generated approximately 60 CD41 + CD42b + platelets and 30 CD41 + CD42b + megakaryocytes on Day 14 for every CD34 + cells seeded on Day 0 (Figure 3C).…”
Section: Resultssupporting
confidence: 86%
“…These criteria ensured that larger cells, microparticles, and GPIIb + & GPIb − (CD41 + & CD42b − ) particles were excluded from our analysis. Omitting GPIIb + & GPIb − is critical as previous groups have shown that these platelet-like particles are not characteristic of functional platelets 12 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PLT components are shuttled and packaged along these extensions, termed proplatelets (proPLTs), before being sheared off by flowing blood [1]. MKs and their PLT progeny have been successfully derived in vitro from CD34 + hematopoietic stem and progenitor cells (HSPCs) from mobilized peripheral blood (mPB) [2, 3] and umbilical cord blood [4-8], as well as MK progenitor immortalized cell lines [9], induced pluripotent stem cells [10-12], and embryonic stem cells [13-15]. …”
Section: Introductionmentioning
confidence: 99%